Utilidad del lactato sérico elevado como factor pronóstico de muerte en sepsis severa - Vásquez-Tirado, Gustavo A. (2015)
Objective: To determine the usefulness of lactate as a prognostic factor of death in severe sepsis. Setting: Hospital Regional Docente de Trujillo. La Libertad. Perú. Material and Methods: A case control study nested in a cohort. We studied a total of 82 adult patients with severe sepsis during the period from June 2012 to April 2013 in whom we determined the usefulness of the lactate level by calculating the Positive and Negative Likelihood Ratio, Relative Risk, Positive and Negative Predictive Value, Sensibility and Specificity. The exposed cohort was constituted by those patients who presented a lactate > 2 mmol/l and the unexposed cohort by those with lactate < 2 mmol/l. Results: Overall mortality was of 54.9 % of the patients, being 92.7% in the group of cases and 17.1% in the group of controls respectively. We found a Sensitivity of 84.4% (CI: 72.7 - 96.1), a Specificity of 91.9% (CI:81.7 - 100.0), a Positive Predictive Value of 92.68% (CI: 83.5 - 100-0), a Negative Predictive Value of 82.9 (CI: 70.2 - 95.7), a Positive Likelihood Ratio of 10.4 (CI: 3.5 - 31.0), a Negative Likelihood Ratio of 0.2 (CI: 01 - 0.3) and a Relative Risk of 5.4 (CI: 2.8 - 10.7). Conclusion: Cancer, COPD, peripheral arterial disease, diabetes, heart failure, impaired baseline functional status; and overall burden of comorbidity are the main risk factors associated with hospital complications in older adults.